PRODUCT LABEL INNOVATION DESIGN AS A FACTOR FOR INCREASING THE COMPETITIVENESS OF MSME PRODUCTS - Martia, Dina Yeni; Soebroto, Nina Woelan; Kodir, Moch. Abdul; Pradana, Bagas Putra; Senoaji, Aditya Rizqi (Politeknik Negeri Semarang, 2024)
In the era of industrial revolution 4.0 that is currently being experienced, it requires all aspects of life to be able to adapt to the modernization that is occurring, such as the rapid flow of information, globalization and the economy. The method used in this research uses SWOT (Strengths, Weaknesses, Opportunities, and Threats). Where the results of SWOT are a challenge for companies to survive amidst current developments, so as not to be swept away by the current developments. Companies are required to always innovate their products. SME competitiveness is reflected in product competitiveness and organizational competitiveness. The main indicators of product competitiveness are product value/price and consumer satisfaction, while the main indicators of organizational competitiveness are profit and human resources (HR). High innovation, both process innovation and product innovation, will increase the ability of SMEs to create higher quality products. High product quality will increase competitive advantage in SMEs which ultimately has an impact on the performance of SMEs themselves. Without a strong brand image or brand image, it will be difficult for a company to attract new customers and retain existing ones. Brand trust will determine consumer loyalty to the brand and trust will have the potential to create high-value relationships. Therefore, innovative product label design is used to increase product selling value. Keywords: Labels, MSMEs, SWOT